2022
DOI: 10.3390/ijms24010449
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxidation and Iron Metabolism: Two Corner Stones in the Homeostasis Control of Ferroptosis

Abstract: Regulated cell death (RCD) has a significant impact on development, tissue homeostasis, and the occurrence of various diseases. Among different forms of RCD, ferroptosis is considered as a type of reactive oxygen species (ROS)-dependent regulated necrosis. ROS can react with polyunsaturated fatty acids (PUFAs) of the lipid (L) membrane via the formation of a lipid radical L• and induce lipid peroxidation to form L-ROS. Ferroptosis is triggered by an imbalance between lipid hydroperoxide (LOOH) detoxification a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(91 citation statements)
references
References 89 publications
2
89
0
Order By: Relevance
“…It is well established that elevated ROS leads to the accumulation of malondialdehyde (MDA), the end product of lipid peroxidation, causing cytotoxicity and damage. 37 Consistent with the ROS levels, LCA also reduced DONincreased MDA concentrations (Figure 2B). Second, analysis of the RNA-seq data set revealed that genes involved in antioxidation were downregulated during DON exposure, while the expression of oxidative genes was upregulated (Figure 2C).…”
Section: Lca Treatment Reserves Don-caused Cell Death Via the Inactiv...supporting
confidence: 75%
See 1 more Smart Citation
“…It is well established that elevated ROS leads to the accumulation of malondialdehyde (MDA), the end product of lipid peroxidation, causing cytotoxicity and damage. 37 Consistent with the ROS levels, LCA also reduced DONincreased MDA concentrations (Figure 2B). Second, analysis of the RNA-seq data set revealed that genes involved in antioxidation were downregulated during DON exposure, while the expression of oxidative genes was upregulated (Figure 2C).…”
Section: Lca Treatment Reserves Don-caused Cell Death Via the Inactiv...supporting
confidence: 75%
“…First, LCA ameliorated the DON-elevated ROS levels in IPI-2I were measured (Figure A). It is well established that elevated ROS leads to the accumulation of malondialdehyde (MDA), the end product of lipid peroxidation, causing cytotoxicity and damage . Consistent with the ROS levels, LCA also reduced DON-increased MDA concentrations (Figure B).…”
Section: Resultssupporting
confidence: 59%
“…ROS are produced by healthy cells in a highly regulated fashion in order to maintain intracellular redox homeostasis [ 32 ]. Oxidative stress can be described as an imbalance between the production of oxidant species and the antioxidant defenses, which may affect cellular redox homeostasis leading to molecular alterations and thus resulting in cell damage [ 33 ]. In addition, several recent studies have shown that the overproduction of ROS, disruption of the antioxidant stress system and production of oxidative DNA are important mechanisms of osteoblast apoptosis and osteoclastogenesis [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…5,67 The ferritin heavy chain (FTH1) can catalyze the oxidation of Fe 2+ to Fe 3+ , reducing the participation of Fe 2+ in Fenton reactions, decreasing ROS production, and reducing free radical damage to cells and tissues. 68 Therefore, FTH1 expression can inhibit cell ferroptosis by reducing the Fe 2+ content. As shown in Fig.…”
Section: Fibrate-pt(iv) Compounds Triggered Ferroptosis Via Inhibitio...mentioning
confidence: 99%